A new fuzzy multicriteria decision making approach: An application for European Quality Award assessment - Aydin, Serhat; Kahraman, Cengiz; Kaya, Ihsan (ELSEVIER, 2012)
European Foundation for Quality Management (EFQM) Excellence Award is Europe's most prestigious award for organizational business excellence. The award is given to the best performing not-for-profit organizations in Europe. The assessments of award are achieved by using EFQM Excellence Model. The aim of this study is to propose a new integrated approach based on a new analytic hierarchy process and EFQM Model to evaluate the business performance excellence. The proposed method enables experts use different fuzzy scales to evaluate firms according to EFQM Excellence Award scoring system. To demonstrate the applicability of the proposed method, a case study is given. A four level hierarchy is established and four experts evaluate firms. Finally, the global weights of the firms are obtained to rank them. The proposed method is also compared with fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and the obtained results confirm that the proposed method effectively evaluates firms for EFQM Excellence Award. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: European Foundation for Quality; Management Excellence Award; Analytic hierarchy process; Linguistic scale; Fuzzy sets; TOPSIS; Multicriteria decision making; EFQM EXCELLENCE MODEL; PERFORMANCE; CRITERIA; EXTENT; Computer Science